Potencial de interação do quelato de ferro e auxina na nutrição e produção de acerola - Silva, Rafaela de Oliveira (Universidade Federal de São Carlos, 2025)
Iron (Fe) deficiency is one of the main nutritional disorders in human populations, especially in socially vulnerable regions. The acerola tree (Malpighia emarginata D.C.), due to its high vitamin C content and considerable carotenoid value, shows potential for biofortification strategies aimed at combating iron-deficiency anemia. This study aimed to evaluate the interaction and effects of different doses of chelated iron (Fe-EDDHA), in association with the application of auxin (naphthaleneacetic acid – NAA), in acerola plants. The experiment was conducted in a completely randomized design (CRD), in a 3 × 2 factorial scheme, totaling six treatments with four replications. Three iron concentrations (0.0245%, 0.049%, and 0.0735%) were tested, with or without NAA application at 10 mg/L. Physiological variables such as chlorophyll b content, stomatal conductance, and photosystem II efficiency were sensitive to the interaction between iron and auxin, indicating effects on photosynthetic activity, transpiration, and gas exchange. Results showed that increasing iron doses did not necessarily lead to higher nutrient accumulation in fruits, and the highest dose (0.0735%) combined with NAA resulted in plants without fruit production. Differences in iron content between leaves and fruits suggest restrictions on the redistribution of this micronutrient among plant tissues. Auxin application also affected soil parameters such as electrical conductivity and pH, which may have influenced iron absorption. It was concluded that high iron doses and the presence of auxin negatively affect fruit production and iron translocation, indicating the need for adjustments in doses and application methods. Overall, higher iron levels, even when associated with auxin, did not promote greater nutrient accumulation in acerola, highlighting the need for further studies on the mechanisms of iron absorption and translocation. It is suggested that the application of auxin (NAA) may be linked to the inhibition of flowering in plants under higher iron doses, indicating the need for further studies on this interaction.
Potential interaction of iron chelate and auxin in acerola nutrition and yield
Keywords: Malpighia emarginata; Ferro (EDDHA); Ácido naftalenoacético; Nutrição vegetal; Produtividade; Iron (EDDHA); Naphthaleneacetic acid; Plant nutrition; Biofortification; Yield; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL; 2. Fome Zero e Agricultura Sustentável; 15. Vida Terrestre